Long-term results and recurrence patterns from SCOPE-1: a phase II/III randomised trial of definitive chemoradiotherapy +/− cetuximab in oesophageal cancer - Crosby, T; Hurt, C; Falk, S; Gollins, S; Staffurth, J; Ray, R; Bridgewater, J; Geh, J; Cunningham, D; Blazeby, J; Roy, R; Maughan, T; et al. (Springer Nature, 2017)
The SCOPE-1 study tested the role of adding cetuximab to conventional definitive chemoradiotherapy (dCRT), and demonstrated greater toxicity and worse survival outcomes. We present the long-term outcomes and patterns of recurrence.SCOPE-1 was a phase II/III trial in which patients were randomised to cisplatin 60 mg m-2 (day 1) and capecitabine 625 mg m-2 bd (days 1-21) for four cycles +/- cetuximab 400 mg m-2 day 1 then by 250 mg m-2 weekly. Radiotherapy consisted of 50 Gy/25# given concurrently with cycles 3 and 4. Recruitment was between February 2008 and February 2012, when the IDMC recommended closure on the basis of futility.About 258 patients (dCRT=129; dCRT+cetuximab (dCRT+C)=129) were recruited from 36 centres. About 72.9% (n=188) had squamous cell histology. The median follow-up (IQR) was 46.2 (35.9-48.3) months for surviving patients. The median overall survival (OS; months; 95% CI) was 34.5 (24.7-42.3) in dCRT and 24.7 (18.6-31.3) in dCRT+C (hazard ratio (HR)=1.25, 95% CIs: 0.93-1.69, P=0.137). Median progression-free survival (PFS; months; 95% CI) was 24.1 (15.3-29.9) and 15.9 (10.7-20.8) months, respectively (HR=1.28, 95% CIs: 0.94-1.75; P=0.114). On multivariable analysis only earlier stage, full-dose RT, and higher cisplatin dose intensity were associated with improved OS.The mature analysis demonstrates that the dCRT regimen used in the study provided useful survival outcomes despite its use in patients who were largely unfit for surgery or who had inoperable disease. Given the competing risk of systemic and local failure, future studies should continue to focus on enhancing local control as well as optimising systemic therapy.